Pre-pregnancy BMI modifies the associations between triglyceride–glucose index in early pregnancy and adverse perinatal outcomes: a 5-year cohort study of 67,936 women in China - Li Li; Yulai Zhou; Huan Li; Juan Li; Lishi Huang; Weibin Wu (Diabetology & Metabolic Syndrome)
Abstract Background Triglyceride-glucose (TyG) index was suggested as a possible surrogate for insulin resistance and a predictor for cardiovascular diseases and diabetes in the non-pregnant population. However, the relationship between TyG index in early pregnancy and adverse pregnancy outcomes (APOs), and the contribution of pre-pregnancy body mass index (BMI) was still illusive. Methods A large retrospective cohort study involving 67,936 pregnant Chinese women between 2017 and 2022 was conducted. Data collection and laboratory tests were performed during the usual patient care. TyG index was calculated using ln [fasting plasma triglyceride (TG; mmol/L) × 88.5 × glucose (FPG; mmol/L) × 18.02/2]. Multivariable logistic regression models were applied to explore the relationship between TyG index and APOs. Interaction and stratification analyses were performed to assess the influence of pre-pregnancy BMI on the association. In addition, ROC curves were used to evaluate the potential predictive value of the TyG index and pre-pregnancy BMI. Results Positive associations between maternal early pregnancy TyG index and APOs, including gestational diabetes mellitus (GDM), hypertensive disorders of pregnancy (HDP), large for gestational age (LGA) and preterm birth (PTB) were demonstrated (all P < 0.001). Besides, there was a significant interaction effect of maternal pre-pregnancy BMI and TyG on the risk of GDM, HDP and LGA (P < 0.05). Women of pre-pregnancy overweight/obesity (OWO) with TyG index in the fourth quartile were at an increased risk for GDM [adjusted OR (aOR) and 95% CI, 3.82 (3.14–4.64)], HDP [aOR 95% CI, 1.34 (1.10–1.64)], for LGA [aOR 95% CI, 1.78 (1.44–2.19)], and PTB [aOR 95% CI, 1.53 (1.11–2.09)], compared with OWO mothers with TyG in the lowest quartile. In addition, the combination of BMI and TyG enhanced predictive performance for APOs, particularly in women with normal plasma TG and FPG levels. Conclusions Dose–response relationships were identified between elevated maternal TyG index in early pregnancy and APOs. A combination of early pregnancy TyG index and pre-pregnancy BMI may provide predictive value for APOs, even in low-risk women. Thus, early screening of fasting blood lipids and glucose simultaneously may be useful and convenient for the early identification of APOs, both among OWO and low-risk normal-weight women.